Misoprostol attenuates neonatal cardiomyocyte proliferation through Bnip3, perinuclear calcium signaling, and inhibition of glycolysis. (September 2020) - Martens, Matthew D.; Field, Jared T.; Seshadri, Nivedita; Day, Chelsea; Chapman, Donald; Keijzer, Richard; Doucette, Christine A.; Hatch, Grant M.; West, Adrian R.; Ivanco, Tammy L.; Gordon, Joseph W.
Abstract: Systemic hypoxia resulting from preterm birth, altered lung development, and cyanotic congenital heart disease is known to impede the regulatory and developmental pathways in the neonatal heart. While the molecular mechanisms are still unknown, hypoxia induces aberrant cardiomyocyte proliferation, which may be initially adaptive, but can ultimately program the heart to fail in early life. Recent evidence suggests that the prostaglandin E1 analogue, misoprostol, is cytoprotective in the hypoxia-exposed neonatal heart by impacting alternative splicing of the Bcl-2 family member Bnip3, resulting in the generation of a variant lacking the third exon (Bnip3Δ Exon3 or small Nip; sNip). Using a rodent model of neonatal hypoxia, in combination with rat primary neonatal cardiomyocytes (PVNCs) and H9c2 cells, we sought to determine if misoprostol can prevent cardiomyocyte proliferation and what the key molecular mechanisms might be in this pathway. In PVNCs, exposure to 10% oxygen induced myocyte proliferation concurrent with molecular markers of cell-cycle progression, such as Cyclin-D1, which were prevented by misoprostol treatment. Furthermore, we describe a critical role for sNip in opposing cardiomyocyte proliferation through several mechanisms, including reduced expression of the proliferative MEF2C-myocardin-BMP10 pathway, accumulation of nuclear calcium leading to NFATc3 activation, and increased expression of the cardiac maturation factor BMP2. Intriguingly, misoprostol and sNip inhibited hypoxia-induced glycolytic flux, which directly influenced myocyte proliferation. These observations were further supported by knockdown studies, where hypoxia-induced cardiomyocyte proliferation is restored in misoprostol-treated cells by an siRNA targeting sNip. Finally, in postnatal day (PND)-10 rat pups exposed to hypoxia, we observed histological evidence of increased nuclei number and increased PPH3 staining, which were completely attenuated by misoprostol treatment. Collectively, this data demonstrates how neonatal cardiomyocyte proliferation can be pharmacologically modulated by misoprostol treatment, which may have important implications for both neonatal and regenerative medicine. Graphical abstract: Unlabelled Image Highlights: Neonatal cardiomyocyte proliferation is inhibited by the prostaglandin analogue Misoprostol. Misoprostol promotes the expression of a small Bnip3 splice variant called sNip. sNip promotes nuclear calcium signaling to activate NFATc3 and alter BMP expression. sNip and NFATc3 inhibit hypoxia-induced glycolysis, directly impacting proliferation.